Authorship and Identity in the Infancy Gospel of Thomas - Chartrand-Burke, Tony (Toronto journal of theology, 1998)
In the study of early Christian writings it is well known that a text's professed authorship can hold the answers to questions of its audience, its place and time of origin, its underlying theological position and the motives behind its creation. Terence V. Smith has described this phenomenon succinctly in his discussion of the Petrine writings. Christianity, he writes, "comprised a variety of different groups whose individuality was often expressed in part by their adherence to a type of Christian belief associated with a particular apostolic figure. A text written under the name of an apostle could therefore be an expression of one of these groups. This cannot be applied universally, however, for apostolic attribution as a method of self identification is really more a first-, second-or third-century phenomenon than a practice of later centuries. And other texts, featuring important Christian figures as characters rather than as their authors, are not necessarily indicative of sectarian allegiances but instead may be a reflection of hagiographical interests. Still, reservations aside, there is considerable value in weighing the evidence of professed authorship when trying to understand a text's place in Christian history.